Agricultural Products Processing and Storage - Shan, Yang.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Agricultural Products Processing and Storage (APPS) is a peer-reviewed, open access journal committed to publish cutting-edge research in the field of agricultural products processing and storage. The journal aims to publish significant, novel, and high-impact research in the fields of agricultural product processing science, technology, engineering, and nutrition. Additionally, supplemental issues are curated and published to facilitate in-depth discussions on special topics. Topics of interest include but are not limited to: Novel and green processing technology Storage and transportation of agricultural products Agricultural products and nutrients on health and diseases Comprehensive utilization of agricultural resources Biosynthesis Edible produce risk assessment and traceability Edible produce equipment and production line Application of artificial intelligence.
Keywords: Agriculture; Agronomy; Food science; Agriculture; Agronomy; Food Science